Electrochemical system design for CO2 conversion: A comprehensive review - M.S. Sajna (17317051) (2023)
This paper reviews the electrochemical reduction of CO2 and the design of CO2 electrolyzer cells using advanced materials and novel configurations to improve efficiency and reduce costs. It examines various system types based on geometry and components, analyzing key performance parameters to offer valuable insights into effective and selective CO2 conversion. Techno-economic analysis is employed to assess the commercial viability of electrochemical CO2 reduction (eCO2R) products. Additionally, the paper discusses the design of eCO2R reactors, addressing challenges, benefits, and developments associated with reactant supply in liquid and gas phases. It also explores knowledge gaps and areas for improvement to facilitate the development of more efficient eCO2R systems. To compete with gas-fed electrolyzers, the paper presents various approaches to enhance the performance of liquid-fed electrolyzers, leveraging their operation simplicity, scalability, low costs, high selectivity, and reasonable energy requirements. Furthermore, recent reports summarizing the performance parameters of reliable and effective electrocatalysts under ideal operating conditions, in conjunction with different electrolyzer configurations, are highlighted. This overview provides insights into the current state of the field and suggests future research directions for producing valuable chemicals with high energy efficiency (low overpotential). Ultimately, this review equips readers with fundamental knowledge and understanding necessary to improve and optimize eCO2R beyond lab-scale applications, fostering advancements in the promising field. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2023.110467